2022
DOI: 10.5811/westjem.2022.5.55351
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Lung and Colorectal Cancer Screening Uptake Among a Safety-net Emergency Department Population

Abstract: Introduction: A suspected diagnosis of cancer through an emergency department (ED) visit is associated with poor clinical outcomes. The purpose of this study was to explore the rate at which ED patients attend cancer screenings for lung, colorectal (CRC), and breast cancers based on national guidelines set forth by the United States Preventive Services Task Force (USPSTF). Methods: This was a prospective cohort study. Patients were randomly approached in the Eskenazi Hospital ED between August 2019–February 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
4
2
1
Order By: Relevance
“…Despite the fact that only 8.3% of participants reported that COVID-19 delayed their cancer screening, our findings found relatively high rates of patients overdue on screening compared to past studies conducted in the ED prior to the pandemic (overdue rates 12–33% for cervical, 9 11 12–46% for breast, 5 , 10 12 and 17–46% for CRC screening 5 , 12 , 13 ). Our higher rates of overdue screenings were probably due not to the pandemic but may have been related to the characteristics of our patient population.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Despite the fact that only 8.3% of participants reported that COVID-19 delayed their cancer screening, our findings found relatively high rates of patients overdue on screening compared to past studies conducted in the ED prior to the pandemic (overdue rates 12–33% for cervical, 9 11 12–46% for breast, 5 , 10 12 and 17–46% for CRC screening 5 , 12 , 13 ). Our higher rates of overdue screenings were probably due not to the pandemic but may have been related to the characteristics of our patient population.…”
Section: Discussioncontrasting
confidence: 87%
“…Our higher rates of overdue screenings were probably due not to the pandemic but may have been related to the characteristics of our patient population. Our study had much higher percentages of Asian (7%) and Hispanic (30%) participants than other similar studies, which had 1-3% 5,9,10,13 and 7-18%, 5,[10][11][12][13]25 respectively. Additionally, in our study Spanish-speaking patients represented 15% of all participants.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…However, preliminary observations and existing literature suggest that regular outpatients might not have higher uptake rates for cancer screening than of the general population. 7,8 Identifying the reasons behind this could reveal specific barriers or misconceptions, even among those with relatively easy access to healthcare services, thereby guiding targeted interventions to enhance cancer screening rates within this subgroup.…”
Section: Introductionmentioning
confidence: 99%